Proses Involusio Uterus pada Ibu yang Melaksanakan dan Tidak Melaksanakan Senam Nifas di Bidan Praktek Mandiri - Munayarokh Munayarokh; Sri Winarsih; Esti Handayani (Poltekkes Kemenkes Semarang, 2015)
The purpose of this study was to determine differences of the uterine involution process on mother taking and not taking the postpartum exercise in Independent Practice Midwife in region of Borobudur Public Health Center Magelang Regency.This study is a case control analytic study with cross-sectional research design. The subjects in this study were normal postpartum mothers who were given and not given postpartum exercises, each 20 postpartum women. Measuring instrument used is a check-list and empirically with metlin. The result showed that the difference of 6 hours postpartum uterine fundus height in the group that did and did not do postpartum exercise get higher average (14.45) in the group that do postpartum exercise with a deviation standard higher in the group that did exercise postpartum (2,72). Differences of 7 days postpartum uterine fundus height on average get nearly the same, namely 7.1 cm and 7.4 cm with a higher deviation standard in the group that did exercise postpartum (1.02), total decrease in the average is higher on mother doing postpartum exercise (7.35) with a higher deviation standard in the group that did exercise postpartum (2.50). There are differences in the uterine involution process in mothers who take and do not take postpartum exercise with a p-value of 0.000.